Identification Morphology and Magnetic Properties Sedimentary Elements Between Fossils and Outcrops Around the Lusi River: A Case Study of Central Java, Indonesia - Putra, Shandiyano; Akmal, Sumartina Gama; Legowo, Budi; Purnama, Budi; Hascaryo, Agus Tri; Widiyanta, Wahyu; Abdulah, Ilham; Kholish, Nur; Dwiyantarai, Heru; Rifai, Hamdi (Trends in Sciences, 2023)
Lusi River flows in the middle of Grobogan Regency with a length of 234 km and an area of 3,656.78 km2. The warp river has many very diverse ends. One of them is the discovery of deer fossils estimated to be around 30,000 years ago and stored in the Pleistocene layer. There may be still many fossils stored in this layer that have never been studied. It is estimated that 80 % of fossils are incomplete because there are teeth attached to the fossils and the condition of the jaws is still neatly arranged. We get the magnetic susceptibility value around 1.3×10−8 - 37.8×10−8 m3/kg. Vibrating Sample Magnetometer confirm that value of magnetic saturation about 0.071 - 0.176 emu/gr, magnetic remanent about 0.0001 - 0.004 emu/gr, and magnetic coercivity around 10.969 - 115.278 Oe. X-Ray Diffractometer confirm the mineral is Calcite (CaCO3) and Quartz (SiO2). From the results we got, it can be confirmed that the fossils found at the bottom of the Lusi river have the same minerals and elements as environmental sediments. So, fossils can be said to have been sedimented over a long period of time in the Lusi River. HIGHLIGHTS We have some important things in this study: Lusi river is a place we found fossil Lusi river we found a poor magnetic mineral We get the magnetic properties of the transition from paramagnetic to diamagnetic GRAPHICAL ABSTRACT